Airway Mucin 2 Is Decreased in Patients with Severe Chronic Obstructive Pulmonary Disease with Bacterial Colonization - Sibila, Oriol (Ann Am Thorac Soc, 2016)
Rationale: Mucins are essential for airway defense against bacteria. We hypothesized that abnormal secreted airway mucin levels would be associated with bacterial colonization in patients with severe chronic obstructive pulmonary disease (COPD) Objectives: To investigate the relationship between mucin levels and the presence of potentially pathogenic micro-organisms in the airways of stable patients with severe COPD Methods: Clinically stable patients with severe COPD were examined prospectively. All patients underwent a computerized tomography scan, lung function tests, induced sputum collection, and bronchoscopy with bronchoalveolar lavage (BAL) and protected specimen brush. Patients with bronchiectasis were excluded. Secreted mucins (MUC2, MUC5AC, and MUC5B) and inflammatory markers were assessed in BAL and sputum by ELISA. Measurements and Main Results: We enrolled 45 patients, with mean age (±SD) of 67 (±8) years and mean FEV(1) of 41 (±10) % predicted. A total of 31% (n = 14) of patients had potentially pathogenic micro-organisms in quantitative bacterial cultures of samples obtained by protected specimen brush. Patients with COPD with positive cultures had lower levels of MUC2 both in BAL (P = 0.02) and in sputum (P = 0.01). No differences in MUC5B or MUC5AC levels were observed among the groups. Lower MUC2 levels were correlated with lower FEV(1) (r = 0.32, P = 0.04) and higher sputum IL-6 (r = −0.40, P = 0.01). Conclusions: Airway MUC2 levels are decreased in patients with severe COPD colonized by potentially pathogenic micro-organisms. These findings may indicate one of the mechanisms underlying airway colonization in patients with severe COPD. Clinical trial registered with www.clinicaltrials.gov (NCT01976117).